Effect of Garlic Filtrate as An Alternative Anticoagulant for Osmotic Fragility Test (OFT) - Aini; Hijriani, Baiq Isti; Dewi, Fitriani Kusuma; Atfal, Bustanul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Osmotic fragility test (OFT) is an examination conducted to measure the resistance of erythrocytes when exposed to hypotonic saline solutions with various concentrations. The purpose of this study was to analyze the effect of garlic filtrate as an alternative anticoagulant for osmotic fragility test (OFT). The samples used were blood samples with heparin anticoagulant. This study is a pre-experimental study, using NaCl solution with concentrations of 0.2%, 0.3%, 0.35%, and 0.55%. The method used to measure OFT value is spectrophotometric method. The data obtained were analyzed using statistical one way Anova. The results showed the percentage value of hemolysis with garlic filtrate at each concentration was 100%, 99%, 95%, and 5%, respectively. Data analysis using ANOVA showed that there was a significant effect on the effect of garlic filtrate as an alternative anticoagulant on OFT with (p < 0.05) 0.000 < 0.05.